Rapid assessment of oxidative status after stenting in acute coronary syndrome with ST segment elevation - Azamat Zhashkeyev; Zhaxybay Zhumadilov; Shynggys Sergazy (Journal of Education and Health Promotion)
BACKGROUND: This paper investigates the potential of using the express method with the e-BQC device to determine antioxidant levels in patients with ST-segment elevation myocardial infarction (MI) (STEMI) both during the acute phase and 3 months post event. The aim is to evaluate the effectiveness of these parameters as indicators of reperfusion syndrome and disease risk. MATERIALS AND METHODS: This research was carried out in patients admitted to the Intensive Care Unit (CEP) of the Karaganda Pluridisciplinary Hospital during the years 2021–2022. Based on defined inclusion and exclusion criteria, 95 patients with STEMI were selected to determine total antioxidant capacity. In addition, the relationship between fundamental characteristics of oxidation state (OSA) and myocadiac ischemia and effect damage was analyzed, including part of the left bus evaluated by echocardiography. RESULTS: The initial findings indicate that oxidative stress assessment (OSA) does not vary significantly across the different stages of acute MI. The indicators of Vitamin C Equivalent Antioxidant Capacity (AQI) do not show statistically significant differences between the three types of antioxidants, the 3 months of infarction. Second, significant direct correlation between fast-acting (Q1), slow-acting (Q2), and full-load (QT) antioxidant indicators was found. CONCLUSION: The application of the express method to determine antioxidant levels through the e-BQC apparatus of patients with STEMI continues to have doubts in the corrective phase of the oxidation process. More research and funding are needed to explore alternative approaches or additional markers to improve the accuracy and availability of oxidative stress assessments in the treatment of MI.